"Even Being a Citizen Is Not a Privilege Here": Undocumented Latinx Immigrant Youth and Perceptions of Racialized Citizenship. Issue 1 (January 2023) - Rodriguez, Sophia; Macias, Eric
This three-year multi-site ethnographic study centers undocumented high school youth's ( N = 53) perspectives on citizenship. Challenging legal conceptions of citizenship, the article advances the notion of racialized citizenship, which is grounded in youth experiences and argues that deeper racial meanings and hierarchies undergird categories of citizenship. By highlighting a nuanced context of reception in the U.S. Southeast, the authors document how youth are racialized in school-community contexts and their perceptions of citizenship. This ethnographic work humanizes undocumented student's experiences and urges educators and policymakers to reject pervasive anti-immigrant discourses and practices.